Atomic-level insights into transition mechanism of dominant mixing modes of multi-component fuel droplets: From evaporation to diffusion. (15th November 2021) - Gong, Yifei; Luo, Kai Hong; Ma, Xiao; Shuai, Shijin; Xu, Hongming
Highlights: Intermolecular interactions in two dominant mixing modes have been investigated. Transition characteristics of the fuel are decided by intermolecular interactions. Fuel clusters form in the mixing layer where the transition happens. Abstract: For a multi-component hydrocarbon mixture under supercritical conditions, especially for fuels injected into compression ignition engines, the mechanism for the transition of the dominant mixing mode from evaporation to diffusion is not well established. In this paper, evaporation processes of a six-component hydrocarbon fuel (13.16 mol% toluene, 13.81 mol% n-decane, 22.30 mol% n-dodecane, 24.60 mol% n-tetradecane, 14.66 mol% n-hexadecane and 11.47 mol% n-octadecane) droplet in nitrogen environments were studied using molecular dynamics (MD) simulations, in comparison with those of three-component and single-component fuel droplets. The ambient pressure ranged from 2 MPa to 16 MPa and the ambient temperature ranged from 750 K to 1350 K. Results indicated that the transition characteristics of the mixed fuel were not the linearly weighted average of the physical properties of individual components in the mixture based on their mole fractions. The reason why there is a limitation on the maximum transition temperature when diffusion dominates the fuel-ambient gas mixing process under high pressures has been discussed. The average resultant force on a fuel atom of an individual component increases with increasing pressure or decreasing temperature at the supercritical temperature, and diffusion will gradually dominate the mixing process of the fuel. The clustering behavior of fuels under supercritical conditions has also been discussed.